Extreme condition high temperature and high pressure studies of the K–U–Mo–O system. Issue 44 (6th November 2020) - Murphy, Gabriel L.; Kegler, Philip; Klinkenberg, Martina; Wang, Shuao; Alekseev, Evgeny V.
Abstract : The first examples of alkali earth uranyl molybdates synthesised using high temperature and high pressure methods, K2 [UO2 (Mo2 O7 )2 ], K2 [(UO2 )2 (Mo(vi )4 Mo(iv )(OH)2 )O16 ], K3 [(UO2 )6 (OH)2 (MoO4 )6 (MoO3 OH)] and K5 [(UO2 )10 MoO5 O11 OH]·H2 O, are described and characterized. Abstract : Herein the first examples of alkali earth uranyl molybdates synthesised using extreme conditions of high temperature and high pressure (HT/HP) methods, namely K2 [UO2 (Mo2 O7 )2 ], K2 [(UO2 )2 (Mo(vi )4 Mo(iv )(OH)2 )O16 ], K3 [(UO2 )6 (OH)2 (MoO4 )6 (MoO3 OH)] and K5 [(UO2 )10 MoO5 O11 OH]·H2 O, are described and characterised. K2 [UO2 (Mo2 O7 )2 ] forms a monoclinic 2D layered structure in space group P 21 / c that consists of interlinking Mo2 O7 dimers that link isolated UO2 2+ moieties forming [UO2 (Mo2 O7 )2 ] 2− layers which are separated by K + cations. K2 [(UO2 )2 (Mo(vi )4 Mo(iv )(OH)2 )O16 ] forms a disordered triclinic 3D framework structure in space group P 1̄. The structure consists of isolated UO2 2+ moieties connected in a layered configuration via Mo(vi )O6 polyhedra of which the layers are bridged by Mo(iv )O6 polyhedra that are partially positionally disordered by charge balancing K + and bridging Mo 4+ cations. K3 [(UO2 )6 (OH)2 (MoO4 )6 (MoO3 OH)] adopts a disordered orthorhombic 3D framework structure in space group Pbcm consisting of small channels and large cavities built upon corner sharing MoO4 and UO2 2+ moieties that respectively encapsulate ordered and disordered K + cations. K5 [(UO2 )10 MoO5 O11 OH]·H2 O forms a triclinic 3D framework structure in space group P 1̄ consisting of interlinking UO6, UO7 and MoO5 polyhedra which utilise cation–cation interactions between UO2 2+ moieties to create infinite channels parallel to the [001] direction which contain partially disordered K + cations and H2 O molecules. A combination of single crystal X-ray diffraction, bond valence sums calculations and scanning electron microscopy with energy dispersive X-ray spectroscopic measurements was used to characterise all obtained samples in this investigation. The structures uncovered in this investigation are discussed systematically in detail with other members of the broader A + –U–Mo–O system from the literature where the relationship between the degree of pressure applied and U/Mo ratio used during synthesis on the ability to obtain high dimensional structures via condensation and oligomerization of polyhedra is identified and discussed in detail.